Vibration suppression of flexible hose for autonomous aerial refueling based on adaptive boundary compound controller - Hang, Bin; Xu, Bin (Aerospace science and technology, 2024)
The suppression of vibrations in flexible hoses during autonomous aerial refueling (AAR) is crucial for enhancing mission success rates and safety, advancing AAR technology. In this paper, an adaptive boundary compound control (ABCC) strategy is proposed to address the vibration suppression problem of the flexible hose of a tanker subject to the bow wave effect (BWE) of the receiver, state output constraint, and partial actuator failure. Unlike previous studies, this research takes into account the impact of the receiver's BWE on these vibrations. The flexible hose is modeled as a three-dimensional Euler-Bernoulli beam (TDEBB), utilizing partial differential equations (PDEs) to provide a more accurate description of its dynamic characteristics. Furthermore, the proposed ABCC strategy accurately detects all disturbances, ensures that the system state output remains within specified limits, and maintains stability even in the face of actuator failures. Last but not least, numerical comparisons and simulations demonstrate that the ABCC method significantly suppresses hose vibrations and maintains end displacement within a narrow range. •The flexible hose's dynamics are precisely modeled using PDEs.•BWE is quantified using CFD to simplify controller design.•The ABCC strategy effectively reduces hose vibrations, and numerical simulations confirm the method's effectiveness.